Gender analysis of the contribution of urban agriculture to sustainable livelihoods in Accra, Ghana - Adeoti, A.I.; Cofie, Olufunke O.; Oladele, O.I. (Informa UK Limited, 2012)
This article examines the sustainability of livelihoods through urban agriculture (UA): gender dimensions in Accra, Ghana. The population used for the study was the vegetable producers within and around Accra, Ghana. A mix of sampling techniques was followed in choosing UA producers. While a random sampling technique was employed in choosing male UA producers, all female producers who were willing to be interviewed were chosen. In all, 92 male producers and 8 female producers gave consistent responses that were analyzed. The results show that the mean age for male producers is 39.4 years. Female producers are more elderly with a mean age of 49.8 years. The mean year of schooling is 6.4 years for male producers and 7.1 years for female producers. While all the households are involved in irrigated farming, only 13% male and 25% female managed farms practiced irrigated farming alone. The majority of the male and female farmers indicated that high contribution of urban agriculture to their livelihoods. Farm size and access to credit were significant determinants of income from urban agriculture among the respondents.